Representations of the ‘Palestinian Prisoners-Shalit Swap’ in selected Arab and Israeli online news articles - Alhossary, Abeer Barakat; Abdullah, Mohd Faiz Sathivellu (Australian International Academic Centre, 2014)
‘The Palestinian Prisoners-Shalit Swap’ was a major issue in the media coverage in the Middle East for almost five years. This issue refers to an agreement between Israel and Hamas, the dominant political party governing the Gaza Strip, to release the captivated Israeli soldier Gilad Shalit in exchange for 1,027 Palestinian prisoners held in Israeli prisons. Both the Arab and Israeli media played a role in portraying the image of the released Palestinian Prisoners versus the Israeli soldier to the readers worldwide. The study aimed to identify the online media coverage of the Swap by Aljazeera English and Ha’aretz in terms of the manipulation of language to identify the discursive strategies and the linguistic means of self-justification of both news agencies towards this issue .The results of the critical discourse analysis using the Halliday’s Transivity Theory revealed that both news agencies employed material process, verbal processes and relational processes differently to highlight certain characters and actions of the Swap from their viewpoint.